2010
DOI: 10.1038/modpathol.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric detection of peripheral blood involvement by mycosis fungoides and Sézary syndrome using T-cell receptor Vβ chain antibodies and its application in blood staging

Abstract: Peripheral blood involvement has been recognized as an adverse prognostic factor in patients with mycosis fungoides and Sé zary syndrome. However, accurate identification and enumeration of the neoplastic cells in these diseases can be challenging. We assessed the clinical utility of flow cytometric immunophenotypic analysis of T-cell receptor Vb expression in 82 mycosis fungoides and 6 Sé zary syndrome patients, with an atypical T-cell immunophenotype, or abnormal CD4:CD8 ratio, identified from peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…We demonstrate that a 6D gating strategy effectively overcomes individual immunophenotypical variations and provides additional parameters to visually separate presumed benign from suspected malignant CD4 T cells. While T cell receptor-β analysis by FC has been proposed as an accurate approach to identify SCs,18 19 we found immunophenotypical analysis to be sufficient for SC identification when appropriate antibody combinations and gating strategies were applied.…”
Section: Discussionmentioning
confidence: 85%
“…We demonstrate that a 6D gating strategy effectively overcomes individual immunophenotypical variations and provides additional parameters to visually separate presumed benign from suspected malignant CD4 T cells. While T cell receptor-β analysis by FC has been proposed as an accurate approach to identify SCs,18 19 we found immunophenotypical analysis to be sufficient for SC identification when appropriate antibody combinations and gating strategies were applied.…”
Section: Discussionmentioning
confidence: 85%
“…In peripheral blood, Feng et al 33 previously showed that the immunophenotypically aberrant T-cell subsets in patients with advanced CTCL correspond to lymphoid cells harboring a clonal T-cell receptor Vβ chain usage, supporting the use of immunophenotypic analysis for the identification of neoplastic cells. On skin biopsy specimens from patients with MF, Clark et al 34 showed the presence of T-cell receptor Vβ-restricted clonal T-cell subsets exhibiting high light scatter by FC.…”
Section: Discussionmentioning
confidence: 97%
“…36 Aberrant expression of T-cell markers by malignant T cells further allows for improved gating for Vb clonality analysis, leading to increase detection sensitivity and specificity. 12,37 In this series of 30 peripheral T-cell lymphomas, a wide variety of Vb families was involved (14 out of 25 specific and 5 out of panel families). They were observed at low frequencies, except Vb17 that appeared to be expanded in 5/30 cases (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, analysis in biopsies is more adapted to unambiguous identification of the malignant T-cell clone since, as mentioned previously, clonal circulating T cells are frequently observed in non-malignant conditions, leading to potential confusion between reactive and tumor cells. 17 On the basis of the promising results obtained from blood samples, [11][12][13][14][15][16] we used flow cytometry to assess the expression of 25 Vb chain members of the TCR. Indeed, T-cell clones use a single Vb domain and can thus be identified by the abnormal expansion of one Vb family or by a restricted TCR-Vb repertoire (see Materials and methods).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation